Sensitivity Enhancement of Polymer Optical Fiber Surface Plasmon Resonance Sensor Utilizing ITO Overlayer - Getinet Woyessa; Ole Bang (Sensors)
We present an experimental study of a sensitivity-enhanced surface plasmon resonance (SPR) sensor utilizing a cladding etched multimode polymer optical fiber (POF) coated with a layer of gold followed by an indium tin oxide (ITO) layer. Our findings indicate that POF SPR sensors with an ITO overlayer exhibit higher sensitivity compared to those coated solely with gold. Additionally, increasing the thickness of the ITO layer increases the sensitivity of the sensor at the expense of a broader SPR spectrum. We determined that the optimal ITO thickness for maximizing sensitivity is 25 nm. The sensor coated with 40 nm gold and 25 nm ITO demonstrated a refractive index sensitivity of 2258 nm per refractive index unit (nm/RIU) with a figure of merit and resolution of 10.13 <semantics>RIU−1</semantics> and <semantics>2.74×10−4 RIU</semantics>, respectively, within the range of 1.33 to 1.37 RIU. Notably, this sensitivity is 70% greater than that of a POF SPR sensor coated only with 40 nm gold. Long-term stability tests conducted in a hydrated environment confirmed that the ITO layer remains unaffected over time and that the maximum SPR wavelength drift was only 1.2 nm. The standard deviation of the three-round measurements also revealed that the sensor has good repeatability. We believe that this sensor offers a simple structure and a relatively easy fabrication process, eliminating the need for side polishing while providing a large interaction area, making it a promising candidate for high-sensitivity biosensing applications.